BAHASA INDONESIA DI THAILAND MENJADI MEDIA DIPLOMASI KEBAHASAAN DAN BUDAYA DI ASEAN MELALUI PENGAJARAN BIPA - Refa Lina Tiawati, M.Pd (Universitas PGRI Sumatera Barat, 2015)
In the effort to introducing and consolidating Indonesian language to the world and ASEAN level, there are a few of options but teaching and mastering Bahasa Indonesia (BI). Through the teaching of Bahasa indonesia for foreign speaker (BIPA), it can be a media of language and culture diplomacy and brings indonesian language as lingua franca in ASEAN community, as happen in Thailand. Therefore, some efforts need to be done in order to realize that through the teaching of BIPA. to increase the interest in learning BI in abroad, to improve the image of the Indonesia as a nation and make BI as Lingua franca, which 1.System BIPA teaching abroad, 2) the material of BIPA, the BIPA learning is not always teach people about the language but also includes material about the culture and Indonesian literature. 3) the purposes of teaching BIPA, to prepare Indonesian language tobe lingua franca in the Asean community.